Weissbuch Gastroenterologie 2023/24 Erkrankungen des Magen-Darm-Traktes, der Leber und der Bauchspeicheldrüse - Gegenwart und Zukunft - Lammert, Frank; Jansen, Petra Lynen; Lerch, Markus M.; Wedemeyer, Heiner (De Gruyter, 2023)
After cardiovascular illnesses, non-malignant diseases of the digestive tract are the most common illnesses affecting Germans, resulting in around 2 million hospitalizations every year. With the updated White Paper, the German Society for Digestive and Metabolic Diseases (DGVS) offers a validated scientific and statistical foundation to underpin the discussion of the present and future status of gastrointestinal diseases in Germany.